Exploring the Influence of Employee Behaviour, Digital Banking and Customer Adjustment on Bank Performance During Covid Pandemic (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Covid-19 pandemic has significantly influenced  all sectors of economy. Banking sector, being an  integral part of financial system, has also been  largely influenced by such pandemic. Thus, an  attempt is made to assess the performance of  banks during the covid pandemic from customer  perspective. The study analyses the influence  of digital banking and employee behaviour on  bank performance. The impact of customer  adjustment is also examined. Structural equation  modelling is applied for data analysis and  hypothesis testing. The study reveals that there  is a significant influence of digital banking and  employee behaviour on the bank performance.  Whereas customer adjustment has no impact  on the performance of banks during covid-19  pandemic. The findings of the present study  will halp banks to revamp their strategies to  improve their performance by neutralizing the  pandemic effect.
Keywords: Covid Pandemic; Bank performance; Customer adjustment; Employee behaviour